2016
DOI: 10.3847/0067-0049/226/2/19
|View full text |Cite
|
Sign up to set email alerts
|

Far-Infrared Line Spectra of Active Galaxies From the Herschel/Pacs Spectrometer: The Complete Database

Abstract: We present a coherent database of spectroscopic observations of far-IR fine-structure lines from the Herschel/ Photoconductor Array Camera and Spectrometer archive for a sample of 170 local active galactic nuclei (AGNs), plus a comparison sample of 20 starburst galaxies and 43 dwarf galaxies. Published Spitzer/IRS and Herschel/ SPIRE line fluxes are included to extend our database to the full 10-600 μm spectral range. The observations are compared to a set of CLOUDY photoionization models to estimate the above… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
120
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 90 publications
(132 citation statements)
references
References 276 publications
(123 reference statements)
12
120
0
Order By: Relevance
“…From the mid-IR line fluxes measured by Tommasin et al (2008) in the Spitzer/IRS-SH and LH spectra listed in Table 1, we obtain the line ratios of [O iv] Sturm et al 2002), but similar to the ratios found in ULIRGs, usually associated with strong star formation (Armus et al 2006(Armus et al , 2007 Table 2), which are more robust diagnostics for the relative AGN/starburst contribution under harder radiation fields (e.g. Lutz et al 1998, Fernández-Ontiveros et al 2016, also suggest a dominant contribution of the starburst component to the lowionisation emission lines. The line ratio diagnostics still apply if we use the [Ne ii] 12.8 µm line flux measured in the VISIR spectrum, which contains about 74% of the flux seen by Spitzer/IRS for the same emission line in a much wider aperture (see Table 1).…”
Section: Ir Spectral Features and Colourssupporting
confidence: 61%
“…From the mid-IR line fluxes measured by Tommasin et al (2008) in the Spitzer/IRS-SH and LH spectra listed in Table 1, we obtain the line ratios of [O iv] Sturm et al 2002), but similar to the ratios found in ULIRGs, usually associated with strong star formation (Armus et al 2006(Armus et al , 2007 Table 2), which are more robust diagnostics for the relative AGN/starburst contribution under harder radiation fields (e.g. Lutz et al 1998, Fernández-Ontiveros et al 2016, also suggest a dominant contribution of the starburst component to the lowionisation emission lines. The line ratio diagnostics still apply if we use the [Ne ii] 12.8 µm line flux measured in the VISIR spectrum, which contains about 74% of the flux seen by Spitzer/IRS for the same emission line in a much wider aperture (see Table 1).…”
Section: Ir Spectral Features and Colourssupporting
confidence: 61%
“…For a black hole mass of M BH ∼ 4 × 10 8 M (see Section 1), and an AGN luminosity of L AGN = 0.5-1 × 10 44 erg s −1 -that is 10-20% of the total IR luminosity based on the flux ratios of the mid-IR fine-structure lines observed by Spitzer/IRS ( [Ne ] -Ontiveros et al 2016), the corresponding Eddington ratio is log(L AGN /L edd ) −2.7. This suggests that the active nucleus is likely in the radio or kinetic mode, thus favouring the jet scenario.…”
Section: Energy and Momentum Balancementioning
confidence: 99%
“…Such low coronal gas densities, though, are unlikely to occur in this AGN. For example, Fernández-Ontiveros et al (2016) using the Spitzer /IRS spectrum for NGC 1386, derived a value of nH = 10 3 cm −3 using the [Ne v] lines in this galaxy. Note also that the emission distribution for all clouds fall out steeply with distance.…”
Section: Channel Maps Coronal Lines and Low-ionization Gasmentioning
confidence: 99%
“…A density of 10 2.97 cm −3 (error interval 10 2.83 -10 3.08 cm −3 ) was derived by Fernández-Ontiveros et al (2016) Oliva (1997) for the coronal line gas. However, theoretical and observational arguments presented by Sharp & Bland-Hawthorn (2010) showed that for ionized gas winds in nearby AGN and starburst galaxies a higher value of f ∼ 0.1 is needed.…”
Section: Agn-driven Outflows Traced By the Coronal Gasmentioning
confidence: 99%